2017
DOI: 10.21273/hortsci10968-16
|View full text |Cite
|
Sign up to set email alerts
|

Bench-top Root-zone Heating Hastens Development of Petunia under a Lower Air Temperature

Abstract: Heating accounts for up to 30% of total operating costs for greenhouse operations in northern latitudes. Growers often lower air temperatures for production to reduce energy costs; however, this causes delays in development even in cold-tolerant crops, such as petunia (Petunia ×hybrida). This delay increases production time and can reduce profitability. Recent studies on low air temperature bedding plant production indicate petunia as a strong potential candidate for using lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Accordingly, this study used a thermostatic plate to heat the base of the cuttings to promote rooting, providing continuous ventilation to ensure a certain temperature difference between the upper and lower parts of the cuttings. In greenhouses, studies have used electric heating wires and plates to heat the substrate [60], and many have used rubber tubes or steam pipes to provide the heat [61][62][63]. Heating wires, tubes, or pipes heat the substrate unevenly; heating plates are better, but they can transfer heat from only one side.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, this study used a thermostatic plate to heat the base of the cuttings to promote rooting, providing continuous ventilation to ensure a certain temperature difference between the upper and lower parts of the cuttings. In greenhouses, studies have used electric heating wires and plates to heat the substrate [60], and many have used rubber tubes or steam pipes to provide the heat [61][62][63]. Heating wires, tubes, or pipes heat the substrate unevenly; heating plates are better, but they can transfer heat from only one side.…”
Section: Discussionmentioning
confidence: 99%
“…Olberg and Lopez (2016) suggested that when root-zone heating > 24°C was utilized during the final stage of poinsettia production, air temperatures could be reduced. Olberg and Lopez (2017) also reported that the root-zone heating of petunia by the bench top heating system can produce high-quality plants in a short period.…”
Section: Local Heatingmentioning
confidence: 95%